Tracing Religious Context in Contemporary Nepali Paintings: A Study of Selected Representative Painters (SIRJANĀ – A Journal Of Arts and Art Education, 2025)
As a channel of expressing religious faith and spirituality, art serves as a bridge between the material and spiritual realms. The practice of blending religious content into art has a long history. Nepal, being a multi-religious country, its arts and architecture are predominantly influenced by Buddhist and Hindu religions. Many contemporary Nepali artists have drawn their artistic inspiration from religious subject matter. Their creative experimentation with religious motifs and elements has given modern Nepali paintings a unique identity. Whether it is a modern rendition of Hindu, Buddhist deities or a recreation of mythical creatures, Nepali painters have left no stone unturned in their artistic exploration with religious content. This research article examines the diverse religious content employed by contemporary Nepali painters in their canvases. It also shows how much our contemporary artists are influenced by religious beliefs and spirituality that they have been brought up with. It reiterates the fact that cultural-religious root serves as the foundation for artistic creation, shaping the content, style, symbolism, and purpose in the art.